Alterations of Hepatic Lipidome Occur in a Gouty Model: A Shotgun Lipidomics Study - Xu X; Jin W; Song J; Hu X; Lu L; Zhang J; Hu C (Dove Medical Press, 2024)
Xiaofen Xu,1,* Wumeng Jin,1,* Jingyi Song,1 Xuanming Hu,1 Lu Lu,2 Jida Zhang,1 Changfeng Hu1 1College of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People's Republic of China; 2Third Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People's Republic of China*These authors contributed equally to this workCorrespondence: Jida Zhang; Changfeng Hu, College of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China, Email zhjd82@tom.com; zhudianzhuifeng@163.comBackground: Liver injury, such as nonalcoholic fatty liver disease, is a common symptom observed in patients with gout/hyperuricaemia. However, the exact mechanisms are still unclear. There is ongoing controversy about whether representative agents like colchicine and febuxostat, commonly used to manage gout, could also help prevent the liver injury. Liver plays a crucial role in uric acid (UA) production and lipid metabolism. Thus, the study aimed to investigate the aberrant lipid metabolism in the liver during injury and the effects of these drugs.Methods: An advanced multi-dimensional mass spectrometry-based shotgun lipidomics technology was employed for class-targeted lipid analysis of cellular lipidomes in hepatic tissue of a gouty model induced by a combination of monosodium urate crystals and high-fat diet with or without treatment with colchicine and febuxostat. Serum UA, blood urea nitrogen, creatinine, proinflammatory cytokines, expression of AMP-activated protein kinase protein, footpad histopathology, and footpad swelling and pain threshold of these mice were assessed to evaluate the progression of gout.Results: Lipidomics analysis clearly demonstrated that the ectopic fat accumulation as well as changes in fatty acyls composition in TAG pool, impaired mitochondrial function resulted by decreased tetra 18:2 cardiolipin, and reduced 4-hydroxyalkenal bioavailability in liver tissue could contribute to liver damage to the gouty model. Treatment with colchicine or febuxostat not only ameliorated gouty symptoms but also corrected these abnormal hepatic lipid metabolism patterns.Conclusion: This study shed light on underlying mechanism(s) for liver injury in gout/hyperuricaemia and suggested that administration of drugs like colchicine and febuxostat could prevent liver injury.Keywords: gout, hepatic lipidome, febuxostat, colchicine, inflammation